Does SSRI Antidepressant Use Influence APGAR Scores? [29N]. (May 2016) - Bakaysa, Stephanie L.; Kelly, Jeannie; Urato, Adam
Abstract : INTRODUCTION: SSRIs have been associated with low APGAR scores, independent of maternal depression, and with preterm birth. Our objective was to determine the association of SSRIs with low APGARs. METHODS: We performed a retrospective matched cohort study on patients who delivered at a tertiary care center from 2009–2014. Women who reported SSRI use on admission were matched to contemporary controls in a 2:1 fashion by completed weeks of gestation and mode of delivery. Fetal anomalies, stillbirths, and multiple gestations were excluded. Odds ratios and 95% confidence intervals were calculated. Fisher's exact test was used to determine significance in the number of APGAR scores <7. RESULTS: 112 SSRI users (2% of deliveries) and 224 controls were included. Women reported using the following: citalopram (n=23), escitalopram (n=4), paroxetine (n=2), fluoxetine (n=34), and sertraline (n=49). 25% delivered preterm. Infants exposed to SSRIs had an increased rate of low APGAR scores at 1 minute (OR 2.0, 95% CI 1.1–3.5, P =.02) and 5 minutes (OR 8.8, 95% CI 2.4–32.0, P =.0009). 1 minute APGAR scores <7 (24% vs 14%, P =.02) and 5 minutes (11% vs 1%, P =.0002) were significantly higher in the SSRI group. CONCLUSION: SSRIs are associated with an increased risk of APGAR scores <7 at 1 and 5 minutes, with an almost 9-fold increased risk of 5 minute APGAR <7. APGAR scores <7 have previously been associated with future cognitive impairment. Further investigation into the impact of SSRI exposure is essential.